Alpha Amylase Inhibitory Activity of Curcumin Analogs and Its Synergy with Ferulic Acid in Vitro - Nafillah, Khoirotun; Ariyani, Helena Devi; Asfirah, Lia Retian (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Curcumin analog compounds are Î±,Î² unsaturated compounds through simplifying the beta diketo group to monoketo, which has better bioavailability and a more stable structure than curcumin compounds. This study aims to determine the Î±-amylase inhibitory activity on symmetric curcumin analog compounds, namely the compounds 2,6-bis(3,4-dimethoxybenzylidine)cyclohexanone (A) and 2,6-bis(3,4-dimethoxybenzylidine)cyclopentanone (B). as well as testing its synergistic interaction with ferulic acid in vitro. The Î±-amylase inhibition test was carried out using an iodine reagent and a starch solution as a substrate. The absorbance value was measured using a UV-vis spectrophotometer (Î» 568 nm), and the % inhibition was calculated. The average value of the optimum Î±-amylase inhibition percentage for compounds A, B, and ferulic acid, respectively is 58.17%; 22.95%, and 93.52%. Based on the synergistic interaction, it was concluded that compounds A and B showed synergistic activity with ferulic acid. The percentage of Î±-amylase inhibition in the concentration ratio of curcumin analog A: ferulic acid (1:8) was 98.65%, and curcumin analog B: ferulic acid (1:4) was 98.37%. This shows that combining compounds between symmetrical curcumin analogs and ferulic acid can increase the activity of antidiabetic drug candidate compounds compared to single compounds. This study offers a new approach by testing the potential combination of curcumin and ferulic acid analogues as Î±-amylase inhibitors in vitro, demonstrating a synergy that has not been widely explored and opening up opportunities for developing more effective natural antidiabetic therapies.